Causas y efectos de la crisis financiera internacional - Pérez, Cristóbal (2013)
The international financial crisis is a process that has an impact on the economies and societies of Latin America. This paper presents the main problems affecting developed economies that make up the European Community. Through the analysis of problems or effects created in a specific country, Spain. Spain’s problems are reflected in most European countries.Their study allows us to understand some of the causes of the crisis and its economic, political and social performance.In brief provides an analysis of the major internal and external causes that generated this storm, and finally there are affecting emerging countries,mainly in Latin America. The analysis includes consideration of the strategy of fiscal policy, monetary and exchange rate policies, as new elements in international relationships. Its hows clearly the interaction between government, international economic relations and banking crisis.